Quality of Care and Survival Outcomes Among Patients With Clinically Localized Prostate Cancer in Nigeria - Musliu Adetola Tolani; Christian Agbo Agbo; Alan Paciorek; Shehu Salihu Umar; Rufus Wale Ojewola; Faruk Mohammed; Ernie Kaninjing; Muhammed Ahmed; Rebecca DeBoer (JCO Global Oncology)
PURPOSEOptimal survival outcomes of prostate cancer are best achieved through high-quality care for curable disease. In Nigeria, various barriers may impede the curative treatment of prostate cancer, yet their impact on care and patient outcomes remains anecdotal. This study assessed treatment quality, survival outcomes, and interhospital differences of these metrics among patients with clinically localized prostate cancer in Nigeria.METHODSA retrospective study of patients with clinical stage T1-T3a, M0 prostate cancer at three tertiary hospitals in Nigeria over a 3-year period was conducted. Data on hospital sites, sociodemographics, clinicopathologic characteristics, quality metrics, imaging used, treatment, and survival status were collected. The primary end point was time from diagnosis to first treatment. Secondary end points were time from presentation to diagnosis, other prostate cancer quality metrics, all-cause survival, and interhospital differences in these metrics. Quality of diagnostics, treatments, and other outcomes were described and compared using Cox regression.RESULTSThis study included 110 patients with a median age of 67 years. Most (n = 66, 61%) had high-risk disease. The median time from tertiary hospital presentation to diagnosis was 31 days. Median time from diagnosis to first treatment of any type was 68 days, with radical radiotherapy was 117 days, and with radical prostatectomy was 104 days. Eighteen percent (n = 20) had guideline-concordant imaging for tumor staging, 67 patients (61%) received any treatment or active surveillance, and retention in care was 42%. Three-year all-cause survival was 41%. There was a significant difference in most quality metrics including guideline-concordant imaging and treatment across the hospital sites.CONCLUSIONTime to treatment was delayed beyond international benchmarks; quality of staging, treatment, and care process were suboptimal; and survival was poor amid geographical disparities in care.